2021
DOI: 10.3390/medicina57080842
|View full text |Cite
|
Sign up to set email alerts
|

The Prospect of Lactoferrin Use as Adjunctive Agent in Management of SARS-CoV-2 Patients: A Randomized Pilot Study

Abstract: Background and Objectives: Preventive, adjunctive and curative properties of lactoferrin have been evaluated since the first wave of severe acute respiratory syndrome coronavirus (SARS-CoV), a viral respiratory disease, emerged 18 years ago. Despite the discovery of new vaccine candidates, there is currently no widely approved treatment for SARS-CoV-2 (COVID-19). Strict adherence to infection prevention and control procedures, as well as vaccines, can, however, prevent the spread of SARS-CoV-2. This study aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…To summarize, Lf should be viewed as a major element in mammalian innate immunity and as a polyvalent regulator that achieves its goal by associating with a variety of factors engaged in infectious or inflammatory activities 82 . There is little question that LF supplementation is an interesting area for further investigation however, the findings of this study do not allow for a firm judgment regarding its potential advantages as a support treatment 160 .…”
Section: Future Perspectivementioning
confidence: 61%
“…To summarize, Lf should be viewed as a major element in mammalian innate immunity and as a polyvalent regulator that achieves its goal by associating with a variety of factors engaged in infectious or inflammatory activities 82 . There is little question that LF supplementation is an interesting area for further investigation however, the findings of this study do not allow for a firm judgment regarding its potential advantages as a support treatment 160 .…”
Section: Future Perspectivementioning
confidence: 61%
“…However, another study showed that the differences regarding reduction in symptoms and laboratory indices between patients receiving approved Egyptian COVID-19 management protocol and patients receiving the same treatment plus lactoferrin were not statistically significant. Further studies with larger samples as well as longer-term trials to understand the role of Lf in treating SARS-CoV-2 are required ( Algahtani et al, 2021 ).…”
Section: Anti Sars-cov-2 Activity Of Whey Proteinsmentioning
confidence: 99%
“…For example, the reported symptoms of fever, dry cough, diarrhea, headache, loss of sense of taste or smell, and fatigue were improved with Lf treatment. Increased serum hemoglobin, lymphocyte count, and platelet count levels were detected at the highest dose of Lf (200 mg, twice daily), while the levels of C-reactive protein declined [ 69 ]. Finally, in a retrospective study on asymptomatic, paucisymptomatic, and moderately symptomatic COVID-19 patients in home-based isolation, Rosa et al compared Lf-treated ( n = 82) to Lf-untreated ( n = 39) patients using bLf unloaded in liposomes.…”
Section: Lactoferrin As a Therapeutic Adjuvant In Respiratory Viral I...mentioning
confidence: 99%